2D Metal‐Free Nanomaterials Beyond Graphene and Its Analogues toward Electrocatalysis Applications. Issue 25 (19th May 2021) - Li, Zhenglong; Chen, Yaping; Ma, Tianyi; Jiang, Yinzhu; Chen, Jian; Pan, Hongge; Sun, Wenping
Abstract: Exploring highly active and low‐cost electrocatalysts is essential to the development of sustainable and efficient energy conversion technologies. 2D nanomaterials with unique electronic structure and physicochemical properties have great potential in constructing advanced electrocatalysts. 2D carbonaceous graphene and its analogs (e.g., reduced graphite oxide, carbon nanosheets) have been extensively studied in this field, while there recently has been considerable attention focusing on other 2D metal‐free nanomaterials (e.g., g‐C3 N4, h‐BN). Here, the recent advances of 2D metal‐free nanomaterials beyond graphene and its analogs toward a wide range of electrocatalysis applications are reviewed. The strategies for constructing advanced 2D metal‐free nanomaterial‐based electrocatalysts are discussed in terms of surface engineering and interface engineering. Finally, perspectives on the challenges and future directions of these unique material systems in the electrocatalysis area are provided. Abstract : 2D carbonaceous materials have been extensively studied in the electrocatalysis field, while there recently has been considerable attention focusing on other metal‐free 2D nanomaterials. This review summaries the recent advances of metal‐free 2D nanomaterials beyond graphene and its analogs toward a wide range of electrocatalysis applications, aiming to provide a deep insight on the challenges and future directions of these unique electrocatalyst systems.